The simple things emagazine (The Simple Things.)
The Simple Things is a beautiful, useful, quirky and fun magazine about taking time to live well. We cover mindfulness and microadventures, eating and growing, forgotten wisdom, home life and slow moments. It's for people who love their lives but want to take the pressure off and remember what’s really important. We like tea & cake, learning stuff, being outside and the satisfaction of a job well done. Do you?